Philosophical and cultural theories of music - Fuente, Eduardo de la; Murphy, Peter, 1956- (Social and critical theory ;, 2010)
This collection brings together philosophers, sociologists, musicologists and students of culture who theorize music through cultural practices as diverse as opera and classical music, jazz and pop, avant-garde and DIY musical cultures, music festivals and isolated listening through the iPod, rock in urban heritage and the piano in East Asia.